Design solutions for improving website quality and effectiveness - Sreedhar, G., 1974-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2016)
"This book is an authoritative reference source for the latest breakthroughs, techniques, and research-based solutions for the overall improvement of the web designing process, featuring relevant coverage on the analytics, metrics, usage, and security aspects of web environments"--Provided by publisher.
Identifying and evaluating web metrics for assuring the quality of web designing / G. Sreedhar -- Enhancing the quality of educational website design through assessment for learning strategies / Wing Shui Ng -- Integrating E-SERVQUAL and Kano model into quality function deployment to improve website service quality: an application to university's website / Dorie Pandora Kesuma [and 4 others] -- Quality assurance aspects of web design / Sandeep Kumar Panda, Santosh Kumar Swain -- Quality measures for semantic web application / Adiraju Prasanth Rao -- Identification of optimal web page set based on web usage using biclustering optimization techniques / R. Rathipriya -- An empirical study of usability metric for websites / Sukhpuneet Kaur [and 3 others] -- Web content management in institutions of higher learning in emerging economies / Gregory Wabuke Wanyembi -- Website link structure optimization / Harpreet Singh, Parminder Kaur -- Web analytics: assessing the quality of websites using web analytics metrics / Balamurugan Balusamy, Venkata Krishna P, Jayashree Sridhar -- Web analytics for web site quality improvement / Ambati Venkata Krishna Prasad, Varaprasad Rao M -- Web analytics: boon for new age entrepreneurship / Himani Singal, Shruti Kohli -- Architecture for improving security in web environment / Varaprasad Rao M, Ambati Venkata Krishna Prasad -- Web based privacy disclosure threats and control techniques / Tithi Hunka, Sital Dash, Prasant Kumar Pattnaik -- Reliability and scalability of service oriented architecture in web services: signature verification / Madana Kumar Reddy C -- Quantitative evaluation of Web2.0 application / Jibitesh Mishra, Kabita Rani Naik.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 01/13/2016).
Keywords: Web sites -- Design; Web site development -- Quality control; Bioclustering optimization techniques; Emerging economies; Online content management; Privacy disclosure; Semantic web applications; Service oriented architecture; Web 2.0 applications; Electronic books